A study on generalized Einstein tensor for an almost pseudo-ricci symmetric manifold - YILMAZ, HÜLYA (My University, 2022)
The object of the paper is to study the generalized Einstein tensor G(X,Y) on almost pseudo-Ricci symmetric manifolds, A(PRS)n. Considering the generalized Einstein tensor G(X,Y) as conservative, cyclic parallel and Codazzi type, it is investigated the properties of such a manifold.
Keywords: Matematik; Diferansiyel Geometri; Temel Bilimler; Mathematics; Differential Geometry; Natural Sciences; Temel Bilimler (SCI); Doğa Bilimleri Genel; ÇOK DİSİPLİNLİ BİLİMLER; MATEMATİK; Natural Sciences (SCI); NATURAL SCIENCES, GENERAL; MATHEMATICS; MULTIDISCIPLINARY SCIENCES; Multidisciplinary; Discrete Mathematics and Combinatorics; Geometry and Topology; Logic; Physical Sciences; Almost pseudo-Ricci symmetric manifold; Codazzi tensor; Conservative; Cyclic parallel; Generalized Einstein tensor; Torqued vector field